Perilaku Petugas Farmasi Tentang Standar Pelayanan Minimal di Instalasi Farmasi Rumah Sakit Awalbros Ujung Batu - Toni Winata; Oktavia Dewi; Emy Leonita; Abdurrahman Hamid; Novita Rany (STIKes Hang Tuah Pekanbaru, 2021)
Pharmaceutical service is a direct and responsible service to patients related to pharmaceutical preparations to achieve definite results to improve the quality of life of patients as stated in Permenkes RI number 35 of 2014 article 1 paragraph 3. This research aims to determine the behavior of pharmacy officers regarding SPM (Minimum Service Standards) at the Awalbros Hospital Pharmacy Installation in Ujung Batu. This research is qualitative research with a phenomenological approach. This research was conducted at the Walbros Ujung Batu hospital installation in July 2020. There were six respondents. The results of the study show that the waiting time for finished drug services is following the provisions of hospital management, which is less than 8 minutes or faster than the service time in the provisions of the hospital and the Ministry of Health, the time for presenting the concocted drugs has not been running with the expected target of fewer than 20 minutes. Because of the numbers of drugs formulated and the limited number of workers working on it. There are no errors in administering the drug, this has been going according to the hospital's standard operating procedures, customer satisfaction has not run perfectly such as waiting time for concocted drugs that are not yet on time, prescription writing according to the formulary has been implemented properly and the formulary guideline document is continuously revised, and the implementation of minimum service standards consistently applied during the Covid-19 pandemic.